The Contribution of Two Big Five Personality Types (Extraversion and Conscientiousness) as Protective Factors Against Suicidal Ideation - Damanik, Dwi Sandra Khoirun Nissa; Nurmina (CAUSALITA : Journal of Psychology, 2025)
This study aims to examine the contribution of two Big Five personality traits (extraversion and conscientiousness) as protective factors against suicidal ideation. The research employed a quantitative method with a total of 100 respondents who reported experiencing suicidal ideation. The sampling technique used was non-probability sampling with a purposive sampling approach, and data were collected through questionnaires. The instruments used included the suicidal ideation scale, the extraversion scale, and the conscientiousness scale. Data analysis using multiple regression techniques revealed the following results: (1) extraversion had a significant negative contribution as a protective factor against suicidal ideation, accounting for 17.17%; (2) conscientiousness also had a significant negative contribution as a protective factor against suicidal ideation, accounting for 16.37%; and (3) both variables together contributed negatively and significantly to protection against suicidal ideation, with a combined contribution of 21.7%.